The Implementation of Authentic Assessment to Assess Students' Higher Order Thinking Skills in Writing at MAN 2 Tulungagung - Muthohharoh, Setyani Rohmatul; Linggar Bharati, Dwi Anggani; Rozi, Fahrur (Universitas Negeri Semarang, 2020)
PISA (Program for International Students’ Assessment) which focuses o three basic literacy stated that Indonesian students are in low position it is caused by the low ability of Indonesian teachers in writing questions of HOTS. Therefore, the 2013 Curriculum demands the teachers to use authentic assessment concerning about Higher Order Thinking Skills. This study aimed to investigate the implementation of authentic assessment to assess students’ Higher Order Thinking Skills in writing at MAN 2 Tulungagung. This study was qualitative research by using case study research design. Two English teachers (teacher SS and teacher IO) were observed by using interview guide, observation checklist, and document observation checklist. The data were then collected and analyzed based on Miles and Huberman (1994, p. 10). The results of the study revealed that in implementing authentic assessment to assess students’ Higher Order Thinking Skills, these two English teachers did not share rubric and implement self-assessment for the students because of time limitation. To overcome the difficulties, they managed the time effectively and efficiently. Furthermore, they were interested in walking around the students to know the students’ understanding. This study will give insight about the implementation of authentic assessment which focuses on Higher Order Thinking Skills in writing.